SOME FEATURES OF THE COMMERCIALIZATION OF RESEARCH WORK AND INNOVATION PROJECTS IN THE CONTEXT OF EURASIAN INTEGRATION - I. V. Medynskaya (Дискурс)
The influence of the integration process on commercialization is connected with the development of scientific and technological progress, which generates innovations in all sectors of the economy and expansion of business at the global level. In the modern community, the issues of the commercialization of innovations are strategically important, without them it is impossible to ensure the effective development of enterprises and economy as a whole. In the context of Eurasian integration, a significant trend in the development of the entire world community is the cooperation of the member countries of the Eurasian Economic Union, which can radically change the current status quo in the global economy. The article examines the problems and prospects of the commercialization of innovations in the context of the Eurasian integration. The features of the commercialization process in different activity areas of the service sector and with different types of consumers are presented. It is shown that the diversification processes under modern conditions of integration and globalization are a stimulus to the development and effective use of the innovative potential of research organizations and industrial enterprises of various industries that implement entrepreneurial type strategies.